(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In an electric vehicle (EV), the high speed motor effectively lowers the motor. Switched Reluctance Motors (SRM) are suitable for high speed drives due to the simple and dependable rotor design. However, there is a disadvantage in that there is significant trembling and acoustic noise. The difficulty of constructing a torque controller is also exacerbated by the intricacy of the unipolar current excitation. The vector control has been suggested as a solution to these SRM issues. However, the SRM has not been subjected to vector control in the high speed zone. This research specifies the driving parameters, such as switching frequency and bus voltage, for applying vector control to the SRM in the high speed zone. The experiment shows that the recommended SRM is capable of realising high output power with less vibration in the high speed region and is controllable by vectors.